Coarse-Grain molecular model development and dynamics simulations study of dodecane droplet spreading at the coal-water interface. (1st September 2021) - Liu, Zechen; Liao, Yinfei; Xu, Ming; Wu, Haosheng; Rudolph, Martin; Wang, Yongtian
Graphical abstract: Highlights: The coal Coarse-Grain model was established based on the Martini force field. The mesoscopic dynamic calculation was performed in the coal-collector-water system. The simulation revealed specific stages of the spreading of dodecane droplet. Abstract: The mesoscopic scale is usually used to realize the dynamics calculation on a larger spatial scale and time scale. However, there have been few dynamic simulation calculations attempted on the mesoscopic scale for coal flotation systems. In this study, based on the Martini force field, the Coarse-Grain (CG) models of coal, dodecane, and water were established, and the dynamics simulations were performed to study the collector droplet spreading at the coal-water interface. The CG dynamics simulations results showed that the interaction between dodecane and coal was a spontaneous process, and dodecane existed as a collector at the coal-water interface. The radial distribution function of dodecane around coal and water indicated that dodecane was more likely to be distributed around the coal, and as far away as possible from the water. The CG dynamics simulations also revealed the specific spreading stages of the dodecane droplet. The dodecane drop first moved in the form of droplets to the coal-water interface in the aqueous phase. Then at the coal-water interface, the circular droplet broke its shape and spread rapidly on the coal surface through the dodecane CG molecules. Finally, the dodecane CG molecules penetrated deeper into the coal surface layer and formed a dynamic and stable oil film. This provided a good attempt and reference for studying the spreading of collector droplets on the coal-water interface.